Shariah Fundamentalisme: antara Narsisisme dan Komoditas Kekerasan - Muhammad Solikhudin (Proceedings of Annual Conference for Muslim Scholars, 2018)
Fundamentalism Shari’ah or violence on the name of religion at this current, seem to still continue to do the whole group of Indonesian society or another. Even in some cases there are a strong shades to perpetuate such desecration. Exclusive religiousness with truth claims unilaterally still to show existence strong enough among religious groups, Muslims especially. They consider their religious understanding that they follow is a truth that is undeniable, and is considered a definite reflection from the source of religious teaching (narsisism). It is thus delivering religious communities to life of conflict vulnerable among humans, fellow adherents of religious different streams, and fellow people of different religion. in addition, understanding this model that will make the people of religion into understanding extreme religious. Religion understood as dogmas die and just take care of the afterlife and the divinity that does not have the ability to provide solutions that delight in solving problems of humanity manifested in contemporary life. This article tries to analyze the problems above by using the approach of phenomenology in sociology so that the readers able to see these problems with an objective view without losing common sense.